Social Aspects of Sport - Knapp, Bobbi (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
Course Description: This course is designed to examine the role of sport in society. Students will use a critical cultural studies approach to examine the meaning of sport within the U.S. To inform our analysis we will investigate a variety of sociological, historical, and cultural perspectives from theoretical and popular sources. With particular attention to the role of gender, sexuality, race, and ethnicity, we will analyze the relationship between sport and culture. Be the conclusion of this course, students should be able to explain how membership or perceived membership in various social groups influences the sporting opportunities available to people. The format of the class may include lectures, student led discussions, videos, guest speakers, and small group work. For each semester hour in the course, students should expect to spend two hours per week preparing for class sessions.